2020
DOI: 10.2147/ijnrd.s240756
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Effect of Peer Support on Hope Among Patients Under Hemodialysis</p>

Abstract: Introduction: Providing social support for patients under hemodialysis treatment can reduce their psychological, social, and physical problems. The present study aimed at determining the effect of peer support on hopefulness in patients under hemodialysis. Methods: This clinical trial with a pre/posttest design was conducted on 128 patients who had referred to the hemodialysis centers of Shiraz University of Medical Sciences in 2019. The patients were randomly divided into an intervention and a control group. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 46 publications
2
15
0
Order By: Relevance
“…A review of the literature revealed that limited studies have been conducted on hope among thalassemia ( 13 ), and hemodialysis patients ( 18 ) and students ( 14 ). Additionally, only a few studies have investigated perceived social support among patients with chronic diseases, such as chronic renal failure ( 6 , 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…A review of the literature revealed that limited studies have been conducted on hope among thalassemia ( 13 ), and hemodialysis patients ( 18 ) and students ( 14 ). Additionally, only a few studies have investigated perceived social support among patients with chronic diseases, such as chronic renal failure ( 6 , 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Pasiar et al the results showed a positive effect of peer education on the hope of patients undergoing hemodialysis. 23 Also, Dant et al in their study stated that peer education can improve the quality of life of diabetic patients. 24 According to what was mentioned above, the main hypothesis of the current study was that peer education is effective on the hope of TM patients.…”
Section: Introductionmentioning
confidence: 99%
“…24 According to what was mentioned above, the main hypothesis of the current study was that peer education is effective on the hope of TM patients. Considering that thalassemia patients due to various reasons suffer from psychological diseases, only a few studies have been conducted to evaluate the effects of educational interventions on the level of hope in these patients 23 . Also, due to the discrepancy in the results of studies such as the results reported by Molazem et al which showed that peer group education had no effect on depression in patients undergoing coronary angiography, 21 the aim of this study was to determine the effects of a peer education program on the hope of TM patients.…”
Section: Introductionmentioning
confidence: 99%
“…As well, improving connection with God among patients from faith-based groups enhances behavioral adaptation required for health management, intensifies courage, optimism, self-control, reduces fear, anxiety, sorrow, and despair (Asadzandi 2017(Asadzandi , 2020Rambod et al 2019). If social, emotional, and spiritual wellbeing has correlations with coping during ill-being (Pasyar et al 2020;Sohail et al 2020), then it is a worthwhile and important to include religiosity as complementary therapeutic approaches.…”
Section: Introductionmentioning
confidence: 99%